Religious communities and ecological sustainability in Southern Africa and beyond - Setume, Senzokuhle Doreen (Journal for the study of religion, 2025)
Climate change and environmental degradation are current realities worldwide. This book is a result of two inter-disciplinary groups in the field, A capacity-building Webinar for Religious Communities and Ecological Sustainability in Southern Africa held on September 1, 2020 (Öhlmann and Stork, 2024, p. 13) and A Conference on Churches in Southern Africa as Civil Society Actors for Ecological Sustainability held at the University of Pretoria in Pretoria, South Africa, from October 28-31, 2019 (Öhlmann and Stork, 2024, p. 14). The book is a result of global engagements such as the International Conference on Religion and Environment held in India during 2024 and the Interdisciplinary Conference on Sustainability and Climate in Religion held in Norway during 2020, therefore presenting a contribution to ongoing debates by bringing a voice from an African religious space. The editors of the volume, who are renowned scholars in the field, make an important observation that "[r]eligion shapes social imaginaries and people's values" (Öhlmann and Stork, 2024, p. 9). As a need to explore the role that religious communities play in ecological sustainability is critical, this book is timely. At the back of our minds we understand that most religions have a strong anthropocentric orientation and Christianity has been accused of such (Mylius, 2018; Setume and Phili, 2020), which has unfortunately contributed to the degradation of the environment. This book raises an important question: What are religious communities doing to attain ecological sustainability in Southern Africa? Given the extent to which the relationship between human beings and the environment has deteriorated over decades, a book that explores the role that religious communities are playing or could play better is very important. Global warming and its effects serve as good indicators of this broken relationship.